High flux, beamed neutron sources employing deuteron-rich ion beams from D2O-ice layered targets. (24th April 2017) - Alejo, A; Krygier, A G; Ahmed, H; Morrison, J T; Clarke, R J; Fuchs, J; Green, A; Green, J S; Jung, D; Kleinschmidt, A; Najmudin, Z; Nakamura, H; et al.
Abstract: A forwardly-peaked bright neutron source was produced using a laser-driven, deuteron-rich ion beam in a pitcher-catcher scenario. A proton-free ion source was produced via target normal sheath acceleration from Au foils having a thin layer of D2 O ice at the rear side, irradiated by sub-petawatt laser pulses (∼200 J, ∼750 fs) at peak intensity ∼ 2 × 10 20 W cm − 2 . The neutrons were preferentially produced in a beam of ∼70° FWHM cone along the ion beam forward direction, with maximum energy up to ∼40 MeV and a peak flux along the axis ∼ 2 × 10 9 n sr − 1 for neutron energy above 2.5 MeV. The experimental data is in good agreement with the simulations carried out for the d(d, n) 3 He reaction using the deuteron beam produced by the ice-layered target.